Firms Response to Misconduct: Evidence from Internal Control - Sarhan, Shatha Ali (2024)
A Master of Science thesis in Accounting by Shatha Ali Sarhan entitled, “Firms Response to Misconduct: Evidence from Internal Control”, submitted in December 2024. Thesis advisor is Dr. Yumin Zhang Perry. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).